Strength analysis and structural optimization of UAV airframe - Ye, Longhai; Zhao, Yanpeng; Zhang, Haifeng; Zhang, Yao; Lv, Jiming; Yang, Zonghan (Frontiers in Mechanical Engineering, 2025)
IntroductionWith the booming low-altitude economy, UAVs drive transformative changes across sectors, but their design must balance lightweight demands and structural integrity. This study conducts static analysis of a quadrotor under hovering, using two optimization methods to enhance performance.MethodsTwo strategies were adopted: mass-constrained structural optimization (maintaining original mass) and unconstrained stiffener optimization (maximizing stiffness/strength without mass limits).ResultsMass-constrained optimization reduced max von Mises stress by 38.8% and displacement from 6.49 mm to 5.91 mm. Unconstrained stiffener optimization achieved 5.2% mass reduction, 60.9% stress reduction, and displacement down to 1.63 mm.DiscussionBoth methods maintain structural strength and boost payload capacity. The stiffener optimization (reinforced rib design) provides a practical solution for heavy-load quadrotor engineering.